2007
DOI: 10.1186/1471-2199-8-38
|View full text |Cite
|
Sign up to set email alerts
|

RNA quality in frozen breast cancer samples and the influence on gene expression analysis – a comparison of three evaluation methods using microcapillary electrophoresis traces

Abstract: Background: Assessing RNA quality is essential for gene expression analysis, as the inclusion of degraded samples may influence the interpretation of expression levels in relation to biological and/or clinical parameters. RNA quality can be analyzed by agarose gel electrophoresis, UV spectrophotometer, or microcapillary electrophoresis traces, and can furthermore be evaluated using different methods. No generally accepted recommendations exist for which technique or evaluation method is the best choice. The ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
72
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(73 citation statements)
references
References 18 publications
(15 reference statements)
1
72
0
Order By: Relevance
“…One post-treatment biopsy was not available for RIN assessment due to the lack of a visible lesion. Similar to previously reported findings [28][29][30], we observed that the RIN is a reliable measure of RNA integrity, as visualized by inspection of electropherograms of biopsy RNA preparations after capillary electrophoresis. The RIN value for a particular tumor RNA preparation was clearly proportional to the intensity of the 28S and 18S rRNA bands on electropherograms (Fig.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…One post-treatment biopsy was not available for RIN assessment due to the lack of a visible lesion. Similar to previously reported findings [28][29][30], we observed that the RIN is a reliable measure of RNA integrity, as visualized by inspection of electropherograms of biopsy RNA preparations after capillary electrophoresis. The RIN value for a particular tumor RNA preparation was clearly proportional to the intensity of the 28S and 18S rRNA bands on electropherograms (Fig.…”
Section: Resultssupporting
confidence: 91%
“…In the latter case, a RIN of 10 represents high quality, intact RNA, while 0 represents completely hydrolyzed RNA. The RIN has been shown to be superior to the 28S/18S rRNA ratio for reliably measuring RNA quality [28][29][30] and is emerging as the ''gold standard'' for RNA quality assessment in mammalian cell lines and tissues [31], including breast tumors [30].…”
Section: Introductionmentioning
confidence: 99%
“…Integrity of obtained RNA was assessed using Agilent 2100 Bioanalyzer (Agilent Technologies, Palo Alto, CA). All samples had an RNA Integrity Number (RIN) greater than 9.4 [26]. Complementary RNA was prepared from 1 lg total RNA, using one-cycle target labeling and a control reagents kit (Affymetrix, Santa Clara, CA).…”
Section: Rna Preparation and Microarray Hybridizationmentioning
confidence: 99%
“…This is in line with a study by Copois et al [10] who compared different methods of RNA assessment-degradometer software [11], 28S to 18S ratio, and an in-house quality scale-with array quality assessed by determination of the 3′ to 5′ ratio of GAPDH and a clustering analysis of full array expression ("dispersion tree"). A similar conclusion was drawn from a small study comparing RNA quality of 24 frozen breast cancer samples assessed by RIN, visual inspection of the capillary electrophoretic trace, and the 28S to 18S ratio [12]. Jahn et al assessed bacterial RNA quality by RIN and found it to be critical for obtaining meaningful gene expression data.…”
Section: Discussionmentioning
confidence: 68%